2016
DOI: 10.1177/0042098016656971
|View full text |Cite
|
Sign up to set email alerts
|

Megalopolis unbound: Knowledge collaboration and functional polycentricity within and beyond the Yangtze River Delta Region in China, 2014

Abstract: Recent work on world city networks, urban polycentricity and megapolitan urban forms share an interest in the economic functionality of inter-city linkages. The intersection of these bodies of literature is in the often overlooked defining features of megalopolitan forms -their being the 'hub' that links national to international urban systems and the 'incubator' within national urban systems (Gottmann, 1976). With this intersection in mind, this paper measures the functional polycentricity of China's Yangtze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…Instead of examining an individual Chinese urban region in detail (e.g. Li and Phelps, ; ; Liu et al ., ; Liu & Wang, ; Zhang & Kloosterman, ; Zhao et al ., ), this study features multiple types of polycentricity change and a larger array of urban regions. It is found that not only the polycentricity but also the polycentricity change is sensitive to scale.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead of examining an individual Chinese urban region in detail (e.g. Li and Phelps, ; ; Liu et al ., ; Liu & Wang, ; Zhang & Kloosterman, ; Zhao et al ., ), this study features multiple types of polycentricity change and a larger array of urban regions. It is found that not only the polycentricity but also the polycentricity change is sensitive to scale.…”
Section: Resultsmentioning
confidence: 99%
“…Hall & Pain, ; Taylor et al ., ) and knowledge (e.g. Li & Phelps, ; ) to analyse the polycentricity of urban regions. However, no dataset is perfect and compromises must be made (Green, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations